Clinicopathological characteristics of distant metastases of adenocarcinoma, squamous cell carcinoma and urothelial carcinoma: An autopsy study of older Japanese patients. Issue 2 (15th September 2017) - Matsuda, Yoko; Seki, Atsuko; Nonaka, Keisuke; Kakizaki, Mototsune; Wang, Tan; Aida, Junko; Ishikawa, Naoshi; Nakano, Yuta; Kaneda, Daita; Takata, Tadayuki; Takahashi‐Fujigasaki, Junko; Murayama, Shigeo; et al.
Abstract: Aim: We aimed to clarify the characteristics of malignancies in older adults focusing on distant metastasis in the whole body. Methods: We retrospectively evaluated 7710 cases of autopsies (4011 men, 3699 women, median age of 80 years), and analyzed the characteristics of metastasis of adenocarcinoma, squamous cell carcinoma and urothelial carcinoma in each organ. Results: The total number of cases with adenocarcinoma, squamous cell carcinoma or urothelial carcinoma was 2856, and most of them were adenocarcinomas. Among them, 1604 had metastatic lesions, and patients with metastasis were younger than those without metastasis. The major primary organs of adenocarcinoma were the stomach, colon, lung, prostate, gallbladder and pancreas, whereas those for squamous cell carcinoma were the lung, esophagus and uterus. Urothelial carcinoma cases were found in the urinary bladder, kidney and ureter. Metastatic adenocarcinomas mainly originated from the stomach, colon, lung, pancreas and gallbladder. Metastatic squamous cell carcinomas were from the lung, esophagus and uterus, whereas the kidney, bladder and ureter were the primary origins of metastatic urothelial carcinomas. Squamous cell carcinoma showed the highest incidence of metastasis, suggestive of it being of an aggressive phenotype. Furthermore, metastatic ability and the preferred metastatic sites varied among primary organs. Conclusions: We revealed an accurate incidence and the characteristics of metastatic cancer in a large‐scale autopsy study of older Japanese patients from one institution. Identifying these features might prompt screening for malignancies, and consequently improve quality of life for older adults.Geriatr Gerontol Int 2018; 18: 211–215 .